2022
DOI: 10.1186/s12885-021-09102-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects in hematologic malignancies treated with chimeric antigen receptor (CAR) T cell therapy: a systematic review and Meta-analysis

Abstract: Background Recently, chimeric antigen receptor-modified (CAR) T cell therapy for hematological malignancies has shown clinical efficacy. Hundreds of clinical trials have been registered and lots of studies have shown hematologic toxic effects were very common. The main purpose of this review is to systematically analyze hematologic toxicity in hematologic malignancies treated with CAR-T cell therapy. Methods We searched databases including PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 77 publications
1
26
0
2
Order By: Relevance
“…Therefore, the use of CD28-based or 4-1BB-based CARs needs to be evaluated with caution. It is notable that 4-1BB-based CAR-T cells appear to be less hematological toxic than CD28-based CAR-T cells ( 110 ), which is perhaps due to their lower activation capacity. Other than 4-1BB, integration of costimulatory domains, ICOS and CD27, can promote CAR-T cell fitness as well ( 111 , 112 ), although further investigations are required to validate these constructs.…”
Section: Approaches To Prolong the Persistence Of Car-t Cellsmentioning
confidence: 99%
“…Therefore, the use of CD28-based or 4-1BB-based CARs needs to be evaluated with caution. It is notable that 4-1BB-based CAR-T cells appear to be less hematological toxic than CD28-based CAR-T cells ( 110 ), which is perhaps due to their lower activation capacity. Other than 4-1BB, integration of costimulatory domains, ICOS and CD27, can promote CAR-T cell fitness as well ( 111 , 112 ), although further investigations are required to validate these constructs.…”
Section: Approaches To Prolong the Persistence Of Car-t Cellsmentioning
confidence: 99%
“…Unlike CRS, IL-6 does not play a prominent role and first line treatment consists of steroids. The situation is similar for hematotoxicity, where therapy is symptomatic with, e.g., transfusions, autologous stem cell boost, and use of thrombopoietin receptor agonists [ 19 , 20 , 21 ]. For instance, it has been shown that CD28 CAR T cells induce more severe adverse effects than 4-1BB CAR T cells, including higher frequency of grade III-IV CRS, grade I-II neurotoxicity and episodes of severe ICANS [ 22 ].…”
Section: Current Limitations Of Car T Cell Therapymentioning
confidence: 99%
“…Countermeasures include the development of multi-specific CARs (e.g., dual or tandem CARs) that target more than one tumor antigen. Signals from clinical trials are encouraging [ 20 , 21 ].…”
Section: Current Limitations Of Car T Cell Therapymentioning
confidence: 99%
“…While eventual recovery from hematotoxicity may be possible, patients are at high risk of succumbing to infections (8). CD34+ HSCB can be a useful therapeutic intervention to shorten the duration of pancytopenia.…”
Section: Manuscriptmentioning
confidence: 99%